1994
DOI: 10.1111/j.1744-7348.1994.tb04118.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen fertiliser on tree/ pasture competition during the establishment phase of a silvopastoral system

Abstract: The establishment phase of an upland silvopastoral system was studied to examine the growth and nutrition of wild cherry (Prunus auium L.) trees under different nitrogen fertiliser treatments. High rates of nitrogen fertiliser exacerbated competition between trees and pasture in a dry year when low fertiliser treatments produced faster tree height growth. When herbicides were not used to control grass growth after the third growing season, tree growth was significantly reduced showing that below-ground competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…In the last year, tree canopy cover was around 60% for S3 treatments compared with 30% of no fertilization treatment (data not published), which may limit pasture response to fertilization. Pasture production is reduced when radiation input to pasture is limited by tree cover, as Campbell et al (1994) observed. This aspect is very important for forest owners if silvopastoral systems are implemented in Galicia because smaller densities should be used in afforestation or reforestation in order to enhance pasture production and also answer to fertilization.…”
Section: Discussionmentioning
confidence: 71%
“…In the last year, tree canopy cover was around 60% for S3 treatments compared with 30% of no fertilization treatment (data not published), which may limit pasture response to fertilization. Pasture production is reduced when radiation input to pasture is limited by tree cover, as Campbell et al (1994) observed. This aspect is very important for forest owners if silvopastoral systems are implemented in Galicia because smaller densities should be used in afforestation or reforestation in order to enhance pasture production and also answer to fertilization.…”
Section: Discussionmentioning
confidence: 71%
“…Tree response to fertilization depends on tree-pasture relationships, which are also affected by soil conditions (Campbell et al, 1994;Rigueiro-Rodríguez et al, 2000;Rigueiro-Rodríguez et al, 2001). Tree growth was enhanced in this study by a low dose of sewage sludge fertilizer, but not by the high dose of sewage sludge fertilizer.…”
Section: Discussionmentioning
confidence: 97%
“…Similar results have been reported by multiple authors following the application of sewage sludge to different tree species, including Douglas fir ( Pseudotsuga menziesii ) (Henry et al, 1994), Monterey pine ( Pinus radiate ) (López‐Díaz et al, 2009), and Canadian poplar ( Populus euramericana ) (Rigueiro‐Rodríguez et al, 2008). These authors showed that tree growth was inversely proportional to pasture production, especially when the pasture production was high due to fertilization (Campbell et al, 1994). Where the conditions are sufficient to allow legume growth, Rhizobium nitrogen fixation can supply a positive fertilization effect on pasture production (Green et al, 1999).…”
Section: Discussionmentioning
confidence: 99%